Investigation of stx2 eae+ Escherichia coli O157:H7 in beef imported from Malaysia to Thailand - Sukhumungoon, Pharanai; Nakaguchi, Yoshitsugu; Ingviya, N.; Pradutkanchana, J.; Iwade, Yoshito; Seto, Kazuko; Radu, Son; Nishibuchi, Mitsuaki; Vuddhakul, Varaporn (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
To gain insight into the microbiological safety of food products routinely traded across international borders in Southeast Asian countries, beef imported from Malaysia to southern Thailand was examined for contamination with Escherichia coli O157 and its subsequent spread into the imported areas. We screened 31 samples exported from Malaysia and 36 domestic Thai samples. Isolation methods including an O157 antigen-targeted immunomagnetic separation technique, screening on CHROMagar O157 medium, and serotype confirmation of E. coli isolates by specific agglutination tests were employed. Fourteen strains of E. coli O157:H7 were isolated from eight Malaysian samples (25.8%) and six strains from four Thai samples (11.1%). These strains were of the stx1- stx2+ eae+ genotype except one Malaysian strain which was of the stx1 - stx2-eae+ genotype. All 19 O157:H7 strains possessing the stx2 gene produced little or no Stx2 (reversed passive latex agglutination titer ≤ 4). Of the 19 strains, five Malaysian (38.5%) and two Thai (33.3%) strains exhibited resistance to a set of antibiotics. Finally, the results of two DNA fingerprinting analyses (O157 IS-printing targeted to IS629 and pulsed-field gel electrophoresis, PFGE) of the O157:H7 strains possessing the stx2 gene, indicated that the Malaysian and Thai strains are closely related. Therefore, E. coli O157:H7 might be transferred from Malaysia to southern Thailand through beef trade.